Physicalités en transition : le cas des barrages hydroélectriques dans les vallées alpines françaises - Emmanuelle Santoire; Jean Desroche; Romain Garcier (Revue de Géographie Alpine)
This article aims to think afresh about the materiality of hydropower dams in Alpine valleys, an old-new energy hotspot expected to resume its central position on the renewable stage. It asks a simple question: does the energy transition agenda affect the materiality of infrastructures which remains ostensibly identical? To answer this question, we use Philippe Descola’s distinction between materiality and physicality and apply it to a case study of the Sautet hydroelectric dam in the French Alps. Indeed, the European energy transition is partly based on the realization of a single liberalized market and the competitive renewal of dam concessions is a key step in this process. Yet, we argue that amidst these changes, the materiality of the studied dam remains substantially the same, while its physicality changes for strategic reasons. Local opposition to liberalization engages a re-evaluation of the physicality of dams (i.e., the way they are supposed to function) in three aspects: their role in river regulation; their territorial dimension; and their financial and fiscal mediating role. The study shows that hydroelectric materiality is a relational element, subject to interpretation between competing values and interests.